Utilizing Sulawesi Folktales Into The Teaching Of Reading Comprehension - Rahmawati Upa; Heryanto Mangalik (Universitas Cokroaminoto Palopo, 2018)
Utilizing local wisdom into the teaching process has been a national agenda in Indonesia Curriculum today but it commonly pay less attention by the teacher including EFL teachers. Meanwhile Indonesia is well known for its diversity of local wisdom. Local wisdom in this case included folktales. This research was done in order to find out whether or not the utilization of Sulawesi folktales into the teaching of reading comprehension is effective. This research applied quantitative method obtained through pre-test – treatment – post-test. The subjects of this research were the fourth semester students of English Language Education Study Program of Universitas Cokroaminoto Palopo. After having data analysis, then the researcher come to the conclusion that the utilization of Sulawesi folktales into the teaching of reading comprehension is effective to improve the students’ reading comprehension. It is proofed through the mean score of the pretest (5.05) and the mean score of the posttest (7.30). The standard deviation of pretest is 1.27 and the posttest is 0.97, while t-test is 0.001, (α) = 0.05.